Harmonising Theory: Integrating Singing With Grounded Theory Methods - Belinda Densley; Virginia Dickson-Swift; Jane Mills (International Journal of Qualitative Methods)
The integration of singing and song with established grounded theory methods offers readers unique methodological insights. Readers will be guided through the process of including singing and song within grounded theory methods using a worked example that explores the facilitator factors in group singing. We detail innovative approaches to research design including data generation, analysis and dissemination of findings. Specific examples will illustrate how singing and song can be incorporated into interviews, participatory workshops, coding, memo writing, and for the enhancement of theoretical sensitivity. Additionally, we introduce novel concepts such as practice-informed research, song reaching, and song fragments, and explore their implications for developing a grounded theory of group singing. Finally, we offer recommendations for using singing and song in the teaching and application of grounded theory methods.